Evidence-Based Decision Support for Neurological Diagnosis Reduces Errors and Unnecessary Workup. (April 2014) - Segal, Michael M.; Williams, Marc S.; Gropman, Andrea L.; Torres, Alcy R.; Forsyth, Rob; Connolly, Anne M.; El-Hattab, Ayman W.; Perlman, Seth J.; Samanta, Debopam; Parikh, Sumit; Pavlakis, Steven G.; Feldman, Lynn K.; et al.
Using vignettes of real cases and the SimulConsult diagnostic decision support software, neurologists listed a differential diagnosis and workup before and after using the decision support. Using the software, there was a significant reduction in error, up to 75% for diagnosis and 56% for workup. This error reduction occurred despite the baseline being one in which testers were allowed to use narrative resources and Web searching. A key factor that improved performance was taking enough time (>2 minutes) to enter clinical findings into the software accurately. Under these conditions and for instances in which the diagnoses changed based on using the software, diagnostic accuracy improved in 96% of instances. There was a 6% decrease in the number of workup items accompanied by a 34% increase in relevance. The authors conclude that decision support for a neurological diagnosis can reduce errors and save on unnecessary testing.